2008
DOI: 10.3354/meps07415
|View full text |Cite
|
Sign up to set email alerts
|

Spawning synchrony and aggregative behaviour of cold-water echinoderms during multi-species mass spawnings

Abstract: Although many marine invertebrates reproduce by releasing gametes into the water, major spawning events have rarely been observed for cold-water invertebrates. We documented mass spawnings by the sea star Asterias vulgaris and the ophiuroid Ophiopholis aculeata on 6 July 1996 and 2 July 1998, and by these 2 species plus a second ophiuroid Ophiura robusta and the sea urchin Strongylocentrotus droebachiensis on 3 July 2003. In each year, the abrupt spawning events coincided with the first major intrusion of warm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 27 publications
0
41
0
Order By: Relevance
“…In fact, earlier sightings of brittle star spawning in subtidal habitats were mostly in the evenings (Hendler 1991, Hagman & Vize 2003. A recent investigation, however, reported 2 daytime spawning ophiuroids (Himmelman et al 2008). Our experiments showed that O. scolopendrina males could be induced to spawn regardless of whether it was day or night, as long as the tide was low (Fig.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In fact, earlier sightings of brittle star spawning in subtidal habitats were mostly in the evenings (Hendler 1991, Hagman & Vize 2003. A recent investigation, however, reported 2 daytime spawning ophiuroids (Himmelman et al 2008). Our experiments showed that O. scolopendrina males could be induced to spawn regardless of whether it was day or night, as long as the tide was low (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…The low tide is just one such condition we found for Ophiocoma scolopendrina. In other brittle stars, abrupt temperature changes have been implicated (Himmelman et al 2008). The results of our water-level experiment (Fig.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This underscores the importance of in determining sperm to egg ratios for these tests as 11 highlighted elsewhere (Dinnel et al, 1987). Previous studies of fertilization in H. erythrogramma used 10 3 -10 5 sperm ml -1 to achieve fertilization rates > 60% (Evans (Himmelman et al, 2008;Pennington, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, it is reasonable to assume its reproductive cycle and brooding period are related to the seasonal abundance of phytoplankton. Environmental factors such as food availability synchronize reproductive events (Himmelman 1975;Tyler 1988;Gage and Tyler 1991;Smiley et al 1991;Himmelman et al 2008).…”
Section: Reproductive Timing and Environmental Conditionsmentioning
confidence: 99%